Design, performance evaluation and investigation of the dynamic mechanisms of earthworm-microorganisms interactions for wastewater treatment through vermifiltration technology. (December 2020) - Arora, Sudipti; Saraswat, Sakshi; Mishra, Rinki; Rajvanshi, Jayana; Sethi, Jasmine; Verma, Anamika; Nag, Aditi; Saxena, Sonika
Abstract: The study brings insight to earthworms-microorganism's symbiotic interactions for wastewater treatment for the most essential mechanisms (antimicrobial and enzymatic activity) during vermifiltration. The results showed that vermifilter (VF) resulted in effluent with biochemical oxygen demand (BOD) <5 mg/L, chemical oxygen demand (COD) <30 mg/L, coliforms <10 3 MPN/100 mL, signifying higher treatment efficacy. The study reported the microbial community diversity for influent, effluent, filter media, earthworm's body, casts and its coelomic fluid to understand the correlations & symbiosis to decipher the mechanisms. The results further showed that earthworm body were dominated by Gammaproteobacteria, and the percentages arrived to 60% of the microbial species, while VF showed presence of Firmicutes and Actinobacteria, which signifies that earthworms had a profound effect on controlling microbial biomass and improving microbial activity. The protein profiling of the bacteria associated with VF showed that earthworms feeding and earthworm–microorganisms interactions were responsible for enhanced treatment performance. Graphical abstract: Unlabelled Image Highlights: Vermifilter is able to treat institutional wastewater with high removal efficiency. Earthworms-microorganisms interactions are responsible for wastewater treatment. Investigation of dynamic mechanisms of microbial community diversity was explored. Earthworm gut microbial communities were dominated by Gammaproteobacteria . Filter media layer showed presence of Firmicutes and Actinobacteria .